Implementing a Process-Based approach to enhance writing skills in 1st and 2nd graders (2024)
ABSTRACT: This study is an action research project carried out with 1st and 2nd graders of the course kids 1 at Centro Colombo Americano de Medellín, Belén site. The aim of this project was to enhance 1st and 2nd graders’ writing skills in EFL classrooms by implementing a Process-Based approach to writing and integrating effective scaffolding strategies into the activities developed during the course. The data collection methods included teacher observations registered in the student teacher’s journal, one student survey, five class artifacts analysis and a Cooperating Teacher interview. Data was analyzed using the triangulation method with all the tools. The results showed that implementing the Process-Based Approach in the writing workshops enhanced students’ writing skills by improving spelling, vocabulary knowledge, sentence construction, and written language communicative awareness.